TINDAK TUTUR DALAM FILM “SURAT KECIL UNTUK TUHAN” KARYA HARRIS NIZAM: SEBUAH TINJAUAN PRAGMATIK DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA - Julia Ismail (EDUKASI, 2016)
The background of this research is speech act as one important aspect in achieving a desired outcome by the speaker to the hearer. This research aimed to determine the use of locution, illocution, perlocution, in the movie “Small Letter to God” by Harris Nizam. This research uses descriptive qualitative method. Data collection procedure in this study refers to the method to obtain data on the use of language by listening, and implication af speech act against Indonesian language learning at school. Basic techniques in this method are tapping and recording. Data were analyzed using the unified method. The techniques used are referential techniques to describe speech act conversations in the film, and pragmatic techniques to explain the speech acts and intentions of speakers based on speech act theory. This research conclude as follows: (1) in the film of  “Small Letter to God” by Harris Nizam dominating by locution act; (2) speech act illocution found in film consisting of speech act of illocution are representative, directive, komisive, and expressive. The act of illocution speech act was not found in this film; (3) a speech perlocution also found in film conversation. Beside that speech act consisting of locution, illocution perlocution also found in  “Small Letter to God” by Harris Nizam; (4) the findings speech act should be used by teachers in teaching Indonesia language  communicatively  related to pragmatic  topic. Keywords:  Speech Act, Locution, Ilocution, Perlocution, Film.